Transcutaneous Neuromodulation improved inflammation and sympathovagal ratio in patients with primary biliary ssscholangitis and inadequate response to Ursodeoxycholic acid: a pilot study - Hui Yang; Hang Yang; Lixia Wang; Honggang Shi; Bojia Liu; Xue Lin; Qingyong Chang; Jiande D. Z. Chen; Zhijun Duan (BMC, 2020)
Abstract Background At present, ursodeoxycholic acid (UDCA) is internationally recognized as a therapeutic drug in clinic. However, about 40% Primary Biliary Cholangitis (PBC) patients are poor responders to UDCA. It has been demonstrated that Transcutaneous Neuromodulation (TN) can be involved in gut motility, metabolism of bile acids, immune inflammation, and autonomic nerve. Therefore, this study aimed to explore the effect of TN combined with UDCA on PBC and related mechanisms. Methods According to inclusion and exclusion criteria, 10 healthy volunteers and 15 PBC patients were recruited to control group and TN group, respectively. PBC patients were alternately but blindly assigned to group A (TN combined with UDCA) and group B (sham-TN combined with UDCA), and a crossover design was used. The TN treatment was performed via the posterior tibial nerve and acupoint ST36 (Zusanli) 1 h twice/day for 2 weeks. T test and nonparametric test were used to analyze the data. Results 1. TN combined with UDCA improved the liver function of PBC patients shown by a significant decrease of alkaline phosphatase and gamma-glutamyltransferase (γ-GT) (P < 0.05). 2. The treatment also decreased serum IL-6 levels (P < 0.05), but not the level of Tumor Necrosis Factor-α, IL-1β or IL-10. 3. TN combined with UDCA regulated autonomic function, enhanced vagal activity, and decreased the sympathovagal ratio assessed by the spectral analysis of heart rate variability (P < 0.05). 4. There was no change in 13 bile acids in serum or stool after TN or sham-TN. Conclusions TN cssombined with UDCA can significantly improve the liver function of PBC patients. It is possibly via the cholinergic anti-inflammatory pathway. TN might be a new non-drug therapy for PBC. Further studies are required. Trial registration The study protocol was registered in Chinese Clinical Trial Registry (number ChiCTR1800014633 ) on 25 January 2018.